Research on 5G Video Security Communication Technology Based on Massive MIMO - Li, Guozheng; Jiang, Heling; Ikbal, Mohammad A. (Recent Advances in Electrical & Electronic Engineering, 2021)
Background: The paper aimed at studying a large number of classified and sensitive information transmission security issues brought by 5G mobile communication system. Methods: In this paper, the principle of beamforming and its shortcomings are introduced by combining the large-scale MIMO technology and directional modulation technology, and the directional modulation technology based on antenna subset selection and the hybrid array is introduced to realize the safe transmission target. The results show that large-scale MIMO technology has become a key technology of 5G mobile communication, but the factors such as multipath fading in the actual wireless channel have not been fully considered, and the accurate estimation error of channel state information (CSI) will affect the ideal security level it can achieve. Results: The combined application of massive MIMO technology and directional modulation technology in the 5G system brings security to its communication. Conclusion: Directional modulation technology based on signal modulation has become an important research point of the 5G system because it does not need to consider the eavesdropper's computing power and can achieve the purpose of safe transmission by disturbing the signal constellation in the unexpected direction.
Keywords: 5G